Estudio constructivo de la estabilización de Taludes con hormigón lanzado, malla electrosoldada y pernos de anclaje, caso: Estribo izquierdo de la presa, del proyecto Hidroeléctrico Minas San Francisco. - Guevara Duta, Andrea Estefanía (2015)
With the present research is to document a technical report Evidencing the constructive steps carried out in the stabilization of a slope with Shotcreting, and anchor bolts welded mesh electro which can be avoided Any kind of collapse or detachment of large masses of land and achieve Consolidation. a clear concept about slope stabilization will be taken and this information will help to answer questions about this type of project, which will provide security from the start of implementation, it is also useful in any work is related to slope and provides ease in the construction process. We will study the construction system with concrete cast, welded and Bolts for stabilizing slopes where for reasons of space it is not possible to use other methods or where embankments using electro mesh would be technically or economically not viable. This method will study can be adapted to any geometry of the terrain and can be used on slopes of high altitude for stabilization without landslides occur ensuring security, it can also be used in support of tunnel walls, roof supports walls deep excavations. construction projects, where you have to stabilize slopes and there is insufficient information construction process, also this method can be used because it is a useful, economical, fast system and applied in works where it is not possible to use other building systems also run . To carry out this story research supported by the contractor "Harbin Electric Corporation" which provides me with the necessary information and knowledge to develop my research.